Perancangan Karakter Personifikasi Mandau Uyau Man Kan Berbasis Budaya Dayak Kalimantan Timur - Ajeng Tita Negoro; Riri Irma Suryani; Nurhadi Nurhadi (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
This project focuses on the significant role of the gaming industry as an agent for spreading popular culture and global lifestyle from various countries, as well as its potential impact on local culture. Especially in the Indonesian market, the penetration of foreign cultures through digital platforms has become a phenomenon that has an impact on local cultural identity. However, as a successful example, Japan in promoting its traditional culture through media such as games, anime, and other products, provides inspiration for an approach that has the potential to strengthen the sustainability of local culture. This design aims to explain how character design in the game industry can be adopted as a tool to introduce and describe cultural values, myths, and philosophies of the East Kalimantan Dayak tribe. This approach will involve developing character designs that take references from the traditions and local wisdom of the Dayak tribe. The design will be a means of providing a unique and engaging visual experience, while simultaneously responding to concerns about the preservation of traditional culture. The methodology used in this research is a design thinking approach with a 5W+1H analysis approach. These design steps would result in a character called "Uyau Man Kan," which has its roots in the traditional folklore of the Dayak people of East Kalimantan. This character is not only a visual manifestation of the culture, but also a bridge for a deeper understanding of the cultural heritage of the Dayak tribe.